2007
DOI: 10.1501/egifak_0000000161
|View full text |Cite
|
Sign up to set email alerts
|

The effects of refutational text and predict-observe-explain strategies on students’ levels of cognitive conflict and conceptual change*

Abstract: ABSTRACT:The purpose of this study was to assess the effectiveness of two conceptual change strategies; refutational text and predict-observe-explain, to determine if either one is more effective with individual learners or groups of learners. Seventy-three juniors were assigned to group or individual conditions and to one of two experimental treatments. Students studied web materials which were designed to overcome their misconceptions about the nature of matter. Pre-tests and post-tests concerning conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Moreover, group discussions gave the preservice elementary teachers opportunity to share different thoughts as it was declared by Niaz (2010, 2012), White and Gunstone (1992). Additionally, in coherence with the results, the research similarly reported that POE activities promoted understanding of scientific concepts adequately (Akgun & Deryakulu, 2007;Costu, Ayas & Niaz, 2010Kearney, 2004;Searle & Gunstone, 1990;Tao & Gunstone, 1997, 1999.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, group discussions gave the preservice elementary teachers opportunity to share different thoughts as it was declared by Niaz (2010, 2012), White and Gunstone (1992). Additionally, in coherence with the results, the research similarly reported that POE activities promoted understanding of scientific concepts adequately (Akgun & Deryakulu, 2007;Costu, Ayas & Niaz, 2010Kearney, 2004;Searle & Gunstone, 1990;Tao & Gunstone, 1997, 1999.…”
Section: Discussionsupporting
confidence: 71%
“…In order to achieve this transformation, cognitive conflict is frequently stressed as a necessity (Akgün & Deryakulu, 2007;Chan, Burtis, & Bereiter, 1997). Cognitive conflict corresponds to Piaget's notion of disequilibration and the condition of dissatisfaction proposed by Posner et al (1982).…”
Section: Conceptual Change Strategiesmentioning
confidence: 99%
“…Alternative conceptions mentioned above can prevent students from learning new concepts, lead them to misconfigure the events they face in daily life, lead them to create ineffective solutions or no solution when they come up against a problem (Akgün & Deryakulu, 2007). Therefore, students' alternative conceptions should be taken into consideration in order to realize conceptual understanding and conceptual change.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide conceptual change related to the particulate nature of matter, the literature includes studies in which constructivist teaching approach (Demir, 2006), analogies (Tsai, 1999), conceptual change texts enriched with animations (Özmen 2011), computer simulations (Stern, Barnea & Shauli, 2008) and animations (Kelly, Phelps & Sanger, 2004;Chang, Quintana & Krajcik, 2010), microcomputer based laboratory (Pierri, Karatrantou & Panagiotakopoulos, 2008), computer software (Papageorgiou, Johnson & Fotiades, 2008), multi-representational instruction (Adadan, Irving & Trundle, 2009), POE methods with conceptual change texts (Akgün & Deryakulu, 2007) and model-based learning (Adadan, 2014) were used. In this study, PDEODE (predict-discuss-explain-observediscuss-explain) teaching strategy which is different from those mentioned above was used.…”
Section: Introductionmentioning
confidence: 99%